2021
DOI: 10.1161/jaha.121.020979
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Trimethyllysine and Prognosis of Patients With Ischemic Stroke

Abstract: Background Trimethyllysine, a trimethylamine N‐oxide precursor, has been identified as an independent cardiovascular risk factor in acute coronary syndrome. However, limited data are available to examine the role of trimethyllysine in the population with stroke. We aimed to examine the relationship between plasma trimethyllysine levels and stroke outcomes in patients presenting with ischemic stroke or transient ischemic attack. Methods and Results Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…47 The relation between gut microbiota and TIA/AIS is described elsewhere. 4850 In line with our results. an alteration in the composition of gut microbiota after acute central nervous system injury has been previously described.…”
Section: Discussionsupporting
confidence: 92%
“…47 The relation between gut microbiota and TIA/AIS is described elsewhere. 4850 In line with our results. an alteration in the composition of gut microbiota after acute central nervous system injury has been previously described.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma levels of TMAO and choline were measured using liquid chromatography–mass spectrometry as in our previous studies. 17 The methods used for TMAO and choline measurement are described in Data S1 and Table S1 and S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, two studies ( 13 , 24 ) have reported that TMAO is a risk factor for moderate-to-severe cerebral infarction, and an additional study ( 28 ) reported that TMAO is a risk factor for fluctuations in the acute phase of cerebral infarction (finding a 2-point increase in the NIHSS score over 3 days). In addition, four studies ( 12 , 16 , 20 , 23 ) reported a positive correlation between TMAO and a history of cerebral infarction, which further validated the correlation between TMAO and cerebral infarction. All results showed that TMAO influenced the onset, severity, fluctuation, and prognosis of cerebral infarction.…”
Section: Discussionmentioning
confidence: 61%